Mechanisms of developmentally controlled cell death in plants - Van Durme, Matthias; Nowack, Moritz K (Current opinion in plant biology, 2016)
•Programmed cell death (PCD) is a vital aspect of plant development.•PCD is the ultimate differentiation step of specific plant cell types.•PCD is gradually prepared in tight coordination with differentiation.•The actual cell death is a highly controlled and rapidly executed process.•Cell-autonomous partial or complete cell clearance is completed post mortem. During plant development various forms of programmed cell death (PCD) are implemented by a number of cell types as inherent part of their differentiation programmes. Differentiation-induced developmental PCD is gradually prepared in concert with the other cell differentiation processes. As precocious or delayed PCD can have detrimental consequences for plant development, the actual execution of PCD has to be tightly controlled. Once triggered, PCD is irrevocably and rapidly executed accompanied by the breakdown of cellular compartments. In most developmental PCD forms, cell death is followed by cell corpse clearance. Devoid of phagocytic mechanisms, dying plant cells have to prepare their own demise in a cell-autonomous fashion before their deaths, ensuring the completion of cell clearance post mortem. Depending on the cell type, cell clearance can be complete or rather selective, and persistent corpses of particular cells accomplish vital functions in the plant body. The present review attempts to give an update on the molecular mechanisms that coordinate differentiation-induced PCD as vital part of plant development.